Pembuatan dan Pelatihan Penggunaan Web Profile SDN 004 Samarinda Ilir di Kalimantan Timur - Sumadi, Muhammad Taufiq (Jurnal Abdimas Perbanas, 2025)
Based on data released by APJII (Association of Indonesian Internet Service Providers), the number of internet users in Indonesia in 2024 will reach 221,563,479 people from a total population of 278,696,200 people in Indonesia in 2023. This shows that 79.5% of the Indonesian population is currently active in using the internet to support various activities. Internet users are spread across various sectors, one of which is the education sector. SDN 004 Samarinda Ilir has been established since 1988, less than 2 kilometers around the location of SDN 004 there are 6 other schools. It is important for SDN 004 to be able to convince parents of prospective students in order to increase the number of students. To be able to achieve this goal, one way is to promote the school through a web-based application. The proposed solution is in the form of creating and training partner web profiles. Then the selection of the appropriate technology platform, application design, and implementation is carried out. The overall interview results were positive and provided solutions to the problems that had been discussed in the initial stage.